CONCEPTUAL ORIENTATIONS OF CREATION OF SYNERGETIC EFFECT OF CONSOLIDATION AND DIVERSIFICATION OF RESOURCES IN THE IMPLEMENTATION OF THE MECHANISM OF MECHANISM IN - Бебко, Світлана (Journal of Strategic Economic Research, 2022)
The article highlights the specifics and key elements of the methodology for consolidation and diversification of resources in the implementation of the mechanism of cooperation management of higher education institutions. It is substantiated that the development of modern higher education in any country in a globalized world is impossible to imagine outside the process of its internationalization, which takes place in the form of international cooperation. It is determined that the internationalization and integration of higher education in the global and international aspect raises many new questions for theory and practice. The most important of them – what is common and special in education and science, which laws, forms, methods of management are universal, and which operate in the range of specific conditions of different countries, how best to perform the functions of education and science in international activities. national style in education and development of the university as an institution of education, in organizational behavior, management systems, how important these features are to achieve the desired results. It is substantiated that international cooperation in this field supports innovation and job creation in integrated higher education institutions, ensuring the mobility of skills between countries. It is established that the international cooperation of higher education institutions contributes to improving the quality and relevance of their higher education and vocational education and training through regular monitoring of graduates. Taking into account the results of scientific research, the key factors of development of the higher system of Ukraine are identified and analyzed, in particular: significant scientific, technical and intellectual potential, especially in the field of technical, natural and medical sciences; a significant network of higher education institutions that stimulates competition in the market of educational services; high level of access to higher education (almost 90% of secondary school graduates study in higher educational institutions, which is one of the highest rates in the world); orientation of the development of the higher education system taking into account international (including European) criteria and standards, including the implementation of the Bologna Declaration.